Enhancing elementary students' spatial awareness through classroom furniture model-making - Satriaji, Kukuh Rizki; Santosa, Imam; Syarief, Achmad; Wibisono, Andriyanto (Faculty of Art and Design, 2025)
Classroom designs in Indonesia typically follow government standards; however, regional variations in conditions and contexts result in diverse classroom shapes and layouts. This diversity can influence students' spatial understanding and familiarity with their learning environments. This study aims to enhance elementary school students' spatial awareness using 1:10 scale flatpack classroom furniture, designed from child-friendly materials and featuring components that students can assemble independently. This interactive approach allows students to explore and recognize the layout of their classroom through play and simulation in collaboration with teachers and peers. The research methodology included school and classroom observations, teacher discussions, creative experiments, and hands-on workshops with students. The study involved students from two elementary schools in different regions of Indonesia, representing various grade levels. The results revealed that students showed distinct preferences for their work areas within the classroom, which contributed to their comfort and sense of attachment to space. These findings highlight the importance of involving students in activities that foster spatial awareness and territorial understanding. They also offer valuable insights for educators and school stakeholders to create more engaging and adaptive classroom environments. By integrating spatial learning into daily activities, schools can provide a comprehensive learning experience that supports students' cognitive and emotional development while fostering a stronger connection to their learning spaces.